Pengembangan Modul Pembelajaran Kimia Berbasis Augmented Reality - Reski Ramadani; Ramlawati Ramlawati; Muhammad Arsyad (Program Pasca Sarjana UNM, 2020)
The study is research and development that aims to develop augmented reality-based chemistry learning module which is valid, practical, and effective. Augmented reality-based chemistry learning module refers to the 4-D development model by Thiagarajan et. al., which includes the stages of defining, designing, developing and disseminating. This learning modules had been conducted the validation stage by the assessors or experts and gone through field trial, revised by the developer to produce learning module which is valid, effective, and practical. The results of the study reveal that: (1) the assessments of feasibility or validity of the media expert and a material expert are in the very valid category; (2) in the field trial stage to 33 students of grade XI MIA 1 at SMAN 10 Makassar obtained the mean score of 80.00 learning outcomes from an ideal score of 100 with a grade completeness of 82%; (3) the responses of students and teachers respectively with a percentage of 80.38% and 100%, so the module is stated as practical. Therefore, the conclusion of the study is the augmented reality-based chemistry learning module which had been developed using 4D model is valid, practical, and effective to be applied in learning.